DFT calculations on the mechanism of copper-catalysed tandem arylation–cyclisation reactions of alkynes and diaryliodonium salts - Stenczel, Tamás Károly; Sinai, Ádám; Novák, Zoltán; Stirling, András (Beilstein Journal of Organic Chemistry, 2018)
We present a computational mechanistic study on the copper(III)-catalysed carboarylation–ring closure reactions leading to the formation of functionalised heterocycles. We have performed DFT calculations along selected routes and compared their free energy profiles. The calculations considered two viable options for the underlying mechanism which differ in the order of the oxazoline ring formation and the aryl transfer steps. In our model transformation, it was found that the reaction generally features the aryl transfer–ring closing sequence and this sequence shows very limited sensitivity to the variation of the substituent of the reactants. On the basis of the mechanism the origin of the stereoselectivity is ascribed to the interaction of the Cu ion with the oxazoline oxygen driving the ring-closure step selectively.
Keywords: catalysis; DFT calculation; iodonium salts; reaction mechanism; tandem arylation–cyclisation